Practice makes perfect basic Latin - Childree, Randall (New York McGraw-Hill Education, 2014)
"Learn Latin in bite-sized lessons! The key to Practice Makes Perfect: Basic Latin is how manageable the grammar and vocabulary are presented to you. You{8217}re not overwhelmed by it all! Supported by engaging exercises, these 50 units cover all aspects of grammar and vocabulary, giving you a solid foundation in the language. Each unit is three pages in length, and you can expect to be completed with each in 10 to 15 minutes. Features: key grammatical concepts and core vocabulary are absorbed almost effortlessly through exercises; flexibility for self-study or as a complement to your first-year class."--Publisher description.
Includes answer key.
English and Latin.
Keywords: Latin language -- Self-instruction.; Latin language -- Grammar -- Problems, exercises, etc